Case series of wolfram syndrome in Uzbekistan - Sh.T. Sultanova; A.V. Alieva; Z.A. Salikhova; N.E. Ismoilova; M.A. Akhmedova (Journal of Clinical and Translational Endocrinology Case Reports, 2025)
The clinical picture of Wolfram syndrome and the data of 12 patients are described. The diagnosis of Wolfram syndrome takes time, since clinical symptoms appear within several years, and the subsequence of the onset of different components of the syndrome also varies. In the description of this series of clinical cases, we tried to analyze the pattern of appearance of clinical symptoms of Wolfram syndrome. The sequence of development of the entire picture of the disease does not always coincide with the classical course of the syndrome, which complicates timely diagnosis.